Investigating the Relationship between miR210 Upregulation and Hemoglobin Gamma Chain Expression - Seyed Amir Hossein Emami; Shahin Mohammadi; Saeed Kavyani; Masud Soleimani; Shaban Alizadeh; Ehteram Dejbakhsh; Fatemeh Kouhkan; Majid Mossahebi; Hossein Dargahi (Tehran University of Medical Sciences, 2011)
Background and Aim: Micro RNAs are a group of small non-coding RNAs which play an important role in multiple processes such as proliferation, differentiation, apoptosis, and cancer. Recent studies indicate that mir-210 is overexpressed into erythroid linage during the differentiation of hematopoietic precursor. The main goal of the present study is to investigate the influence of mir-210 on the pattern of expression in hemoglobin gamma chain. Materials and Methods: First, K562 cell line was cultured in RPMI1640 media. Then, pre-miR-210 was transferred into K562 cell line by lipofectamin. Finally, the alterations in the pattern of gamma chain expression were analyzed in days 7 and 14 by RT-PCR and real time PCR technique. Results: It was demonstrated that the overexpression of mir-210 in K562 cell line would lead to a 25-fold increase in the expression of gamma chain in comparison with the control group. Data analysis revealed that the change in the pattern of hemoglobin gamma chain expression was meaningful (p<0.002). Conclusion: Based on these data, overexpression of mir-210 can lead to a significant increase in the production of gamma chain. Therefore, more studies in the field may reveal the fact that an increase in mir-210 can be a suitable goal in the improvement of sickle cell anemia and β-thalassemia.